Металлокерамические твердые сплавы: пер. с рус. - Романова Н. И. Нина Ивановна; Чекулаев П. Г. Петр Гаврилович; Дусев В. И. Вячеслав Иванович; Лившиц Т. А. Теодор Адольфович; Курдов М. Н. Михаил Николаевич (Москва, Мир, 1972)
На англ. яз.